Catalyst deactivation analysis on Cu/Zn/Al/Zr catalyst in methanol synthesis via CO2 hydrogenation reaction / Nabilah Hanum Mohd Akhir and Dr Muhammad Zahiruddin Ramli - Mohd Akhir, Nabilah Hanum; Ramli, Muhammad Zahiruddin (2020)
Global warming issue had become most challenging issue which believe due to the increasing of greenhouses gases mainly CO2 that gradually increase the global temperature. Hence, the conversion of CO2 gases to value-added chemical and fuel received a significant attention. In this regard, the hydrogenation of CO2 in methanol synthesis was one of the effective strategies in utilization of CO2 emission. Though, due to the complexities that associated with CO2 high stability, the stability/activation of CO2 into methanol becomes one of challenging issues. Also, the loss over time of catalytic activity of heterogeneous catalyst had been a significant concern in operation plant and has been studied for many industrial catalytic applications. Thereby, this research highlights the recent effective investigation in prepare and characterize a single formulation of multi-metallic Cu/Zn/Al/Zr catalyst. Also, to evaluate the deactivation behavior of Cu/Zn/Al/Zr catalyst during methanol synthesis via CO2 hydrogenation reaction. The deactivation behavior of co-precipitated Cu/Zn/Al/Zr catalysts has been studied over 48h of reaction that associated to their performance in methanol by CO2 hydrogenation reaction. In synthesis of methanol process, the conventional Cu/Zn/Al/Zr catalyst system typically prone to the sintering and coking. Nevertheless, the prove of this deactivation behavior was presented based on the chemical and physical characterization of these catalyst system. The characterization of the fresh and spent catalyst using BET indicated that the Cu particles sites been blocked which decreased surface area of the catalyst sample after the performance testing. Next, TPR analysis shows that the spent catalyst reduction peak area was shifts to a higher temperature which 354.21 oC, it is mainly illustrated the Cu reducibility becomes weaken which decrease of the Cu dispersion and H2 consumption after the reaction takes place. Thus, the result shows that coking is the predominant cause of deactivation of catalyst. In addition, based on the mechanism reaction hydrogenation of CO2, the catalyst system proved that it undergone a deactivation process by carbon deposition.